Gen-Z Awareness of Halal Products when Online Shopping for Cosmetics-Skincare (Case Study on Students in Jambi City) - Bella Arisha; Nurrahma Sari Putri; Suharli AJ (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
Indonesia is a country with a Muslim majority. Based on data from Kemendagri, Indonesia's Muslim population is 237.53 million people with a percentage of 86.9% as of December 31, 2021. Indonesia as a country with a Muslim majority means that it must consume and use halal-certified products. The halal industry is currently growing rapidly. Not only in the food industry but also in other industries. The beauty industry has become a trend among teenagers. Based on BPS data, the cosmetics-skincare industry grew by 5.59% even during a pandemic where almost all industries experienced a decline. With a Muslim-majority country, the beauty industry is required to provide and create halal-certified skincare products. This study was conducted to determine the awareness of Gen-Z in buying halal-certified skincare cosmetics in online shopping. By using the Solvin formula to determine the number of samples. The study was conducted on 396 students in Jambi City. The results obtained show that almost 90% of Gen-Z buying cosmetics-skincare in online shopping see halal certification and use cosmetic local product Indonesia.